"The edge of harm and help": ethical considerations in the care of transgender youth with complex family situations. Issue 3 (2nd April 2020) - Clark, Beth A.; Virani, Alice; Saewyc, Elizabeth M.
Abstract : Health-care providers frequently face clinical ethical dilemmas when working with transgender youth who require hormone therapy but lack parental support for this intervention. Through semi-structured interviews and grounded theory analysis, we explored ethical and clinical decision-making processes of health-care providers, as well as the health care experiences of trans youth with family discordance. We analyzed responses in relation to North American bioethics principles, best interests standard, and the harm principle, exploring issues of autonomy, evidence, and anti-trans bias. We propose an ethically acceptable clinical approach termed parallel process hormone therapy initiation to address the needs of transgender youth with complex family situations.